Semi-active structural vibration control of base-isolated buildings using magnetorheological dampers - Oliveira, Fernando; Botto, Miguel Ayala; Morais, Paulo; Suleman, Afzal (Journal of low frequency noise, vibration, and active control, 2018)
In recent years, several solutions for structural vibration control of buildings have been proposed. In particular, the combination of base-isolated structures with complementary variable damping devices has been successful in reducing the base isolator displacements without increasing the building superstructure response when subjected to earthquake loads. In this paper, a magnetorheological device is installed on a 2-DOF mechanical model mounted on an experimental uniaxial shaking table. A simple numerical simulation model is derived for the experimental setup and it represents a typical base-isolated structure with a semi-active vibration controller. The control law combines a force tracking integral action with a clipped on–off adaptation rule that changes the magnetorheological damping in real time. The effectiveness of the proposed solution is demonstrated for both earthquake-like and real earthquake input ground motions. A comparison between the numerical and the experimental results validates the numerical simulations and it gives confidence in using this model for validation and evaluation of other semi-active control solutions based on magnetorheological dampers.